β -Thalassemia Present in cis to a New β -Chain Structural Variant, Hb Vicksburg [β 75(E19)Leu→ 0] - Adams, Junius G.; Steinberg, Martin H.; Newman, Marsha V.; Morrison, W. Tully; Benz, Edward J.; Iyer, Rathi (Proceedings of the National Academy of Sciences - PNAS, 1981)
Hemoglobin Vicksburg was discovered in a 6-year-old Black boy who had been anemic since infancy. Examination of his hemolysate revealed 87.5% Hb F, 3.4% HbA2, and 7.6% Hb Vicksburg, which had the electrophoretic and chromatographic properties of Hb A. Structural analysis of Hb Vicksburg demonstrated a deletion of leucine at β 75(E19), a new variant. Hb Vicksburg was neither unstable nor subject to posttranslational degradation. The α /non-α biosynthetic ratio was 2.6. Because the proband appeared to be a mixed heterozygote for Hb Vicksburg and β0-thalassemia, Hb Vicksburg should have comprised the major portion of the hemolysate. Thus, Hb Vicksburg was synthesized at a rate considerably lower than would be expected on the basis of gene dosage. There was no reason to suspect abnormal translation of βVicksburgmRNA; in individuals with Hb St. Antoine (β 74 and β 75 deleted), the abnormal hemoglobin comprised 25% of the hemolysate in the simple heterozygote yet was unstable. Deletion of β 75, therefore, would not in itself appear to lead to diminished synthesis. There was a profound deficit of βVicksburgmRNA when measured by liquid hybridization analysis with β cDNA.. The most plausible explanation for the low output of Hb Vicksburg is that a mutation for β+-thalassemia is present in cis to the structural mutation.